2009
DOI: 10.2310/7750.2009.08055
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Quality of Life Impact and Clinical Severity on Adherence to Topical Acne Treatment

Abstract: Adherence to topical acne therapy increases with impact on QoL but decreases with increasing acne severity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
33
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 19 publications
1
33
2
Order By: Relevance
“…In standard clinical practice, patients with greater acne severity have been shown to be less compliant to topical therapy. 17 In a clinical trial setting, these subjects may be more motivated to adhere to treatment, particularly if it is convenient, rapid in onset, and capable of maintaining ongoing improvement.…”
Section: Discussionmentioning
confidence: 99%
“…In standard clinical practice, patients with greater acne severity have been shown to be less compliant to topical therapy. 17 In a clinical trial setting, these subjects may be more motivated to adhere to treatment, particularly if it is convenient, rapid in onset, and capable of maintaining ongoing improvement.…”
Section: Discussionmentioning
confidence: 99%
“…Dreno et al [4] also found a risk of poor adherence of 60% among patients taking a combination of both systemic and topical therapy, and a higher likelihood of poor adherence to the systemic arm of treatment compared to the topical arm (54 vs. 44%, respectively). Other studies utilizing questionnaires and/or single questions to assess adherence have found rates of poor adherence ranging from 76 to 0% [2,3,5,15,16,17]. Studies using objective measures such as not keeping appointments, pill counts, weighing medication, number of medication refills, and electronic caps have reported adherence rates ranging from 28 to 88.3% [6,7,8,18].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have evaluated adherence to acne medications in various parts of the world [2,3,4,5,6,7,8]; however, there are few data specific to Japan. This study was designed to assess adherence among acne patients in Japan, to determine if there are differences in adherence based on type of treatment (topical or oral), and to evaluate the factors that can affect adherence to acne treatment.…”
Section: Introductionmentioning
confidence: 99%
“…In dermatology, it can be assessed on generic scales, generic dermatological scales and disease-specific scales [5,6]. It is important to consider this QoL as part of an overall patient management as it has a positive impact on satisfaction regarding care, compliance and therapeutic outcome [3,7,8,9]. The presence of apparent lesions is associated with reduced QoL, especially in patients <40 years old [10,11] and in patients suffering from acne [12,13,14,15,16].…”
Section: Introductionmentioning
confidence: 99%